Tanggung Jawab Notaris Pengganti Atas Akta yang Dibuatnya Karena Adanya Tuntutan Pihak Ketiga dalam Hal Notaris yang Diganti Meninggal Dunia Sebelum Cuti Berakhir - Rinanti, Ade; Ariawan, Ariawan (Syntax Literate, 2021)
As is known in articl 35 UUJN when the notary dead at the time of running the holiday, the task of notary Office is executed by a substitute notary as a provisional official Notary 30 (thirty) days since the date of notary death. The problem in this research is how is the responsibility of the notary of the deed made because there is a third party submission in the evento that the notary is reimbursedo before the end of leave? And how are the legal efforts of a substitute for the deed he made because there is a third party claim in the event that the notary was changed before the end of leave? The research uses normative juridical methods that are supported by juridically empirical. The data used is a secondary data consisting of primary legal material, secondary legal material and a tertier legal material. Besides, it also used primary data as a supporter of secondary data legal material. The theory of the responsibility of Hans Kelsen and the legal protection theory of Phillipus M. Hadjon is used. The responsibility of the notary public on the deed made because there is a third party guidance in the case of the notarized changed before the expiration of the leave is a permanent substitute responsibility until the death because it has changed its legal status to the provisional Office notary, for that the substitute notary has the same responsibilities. In the event that a replacement notary is proven to commit negligence, a surrogate notary has a civil liability that is to compensate the third party, the responsibility of the notary Public administration receives an oral rebuke, written reprimand, disrespectful termination, and criminal liability in a substitute subject to criminal penalties. A substitute legal remedy for the deed he made because of a third party claim in the event that the notary was changed before the end of leave, i.e. a substitute is entitled to make a repressive law attempt, because the legal status of the substitute was switched to as a notary provisional office.